2015
DOI: 10.1080/15548627.2015.1068489
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of lysosomes activates the MTORC1 signaling pathway in chondrocytes in an autophagy-independent manner

Abstract: These authors contributed equally to this publication.Keywords: autophagy, bafilomycin, bone, chondrocyte, lysosome, MTOR, MTORC1Abbreviations: 3-MA, 3-methyladenine; ACAN, aggrecan; ACP5/TRAP, acid phosphatase 5, tartrate-resistant; ACTB, actin, b; ALPL, alkaline phosphatase, liver/bone/kindey; ATG, autophagy related; ATG5cKO, ATG5 conditional knockout in chondrocytes; BC, avidin-biotin complex; Baf, bafilomycin A 1 ; bGP, b-glycerophosphate; BrdU, bromodeoxyuridine; C5.18 cells, RCJ 3.1C5.18 rat mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
(65 reference statements)
2
30
3
Order By: Relevance
“…Unexpectedly, in this work we observed that lysosomal storage enhances, rather than inhibits, mTORC1 signaling in LSD chondrocytes. Similar observations were recapitulated pharmacologically by others (36), suggesting a chondrocyte-specific response of mTORC1 to lysosomal dysfunction.…”
Section: Discussionsupporting
confidence: 67%
“…Unexpectedly, in this work we observed that lysosomal storage enhances, rather than inhibits, mTORC1 signaling in LSD chondrocytes. Similar observations were recapitulated pharmacologically by others (36), suggesting a chondrocyte-specific response of mTORC1 to lysosomal dysfunction.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study of the role of V-ATPase in long bone growth yielded results that appear to contradict our observations of a role for this enzyme in expression of hypertrophy-associated genes (Newton et al, 2015). In this study, organ cultures of metatarsal bones from 3.5-dayold mice provided the source of chondrocytes; bafilomycin A1 was found to cause an increase in the length of the bones, the size of hypertrophic chondrocytes and the length of the zone positive for collagen type X.…”
Section: Discussioncontrasting
confidence: 55%
“…The protein of p62, a protein associated with autophagosomes and degraded in the autolysosome, is commonly regarded as autophagy substrate protein [45, 46], as a mainly negative regulator of autophagy, activated mTORC1 inhibits autophagy induction through blocking of the initial inducer of autophagy [47, 48]. The p62 is the scaffold protein implicated in selective autophagy which is induced by the stress of cells.…”
Section: Discussionmentioning
confidence: 99%